Molecular and structural facets of c-di-GMP signalling associated with biofilm formation in Pseudomonas aeruginosa. (October 2021) - Banerjee, Priyajit; Sahoo, Pankaj Kumar; Sheenu; Adhikary, Anirban; Ruhal, Rohit; Jain, Deepti
Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen and is the primary cause of nosocomial infections. Biofilm formation by this organism results in chronic and hard to eradicate infections. The intracellular signalling molecule bis-(3′–5′)-cyclic dimeric guanosine monophosphate (c-di-GMP) is a secondary messenger in bacterial cells crucial for motile to sessile transition. The signalling pathway components encompass two classes of enzymes with antagonistic activities, the diguanylate cyclases (DGCs) and phosphodiesterases (PDEs) that regulate the cellular levels of c-di-GMP at distinct stages of biofilm initiation, maturation and dispersion. This review summarizes the structural analysis and functional studies of the DGCs and PDEs involved in biofilm regulation in P. aeruginosa. In addition, we also describe the effector proteins that sense the perturbations in c-di-GMP levels to elicit a functional output. Finally, we discuss possible mechanisms that allow the dynamic levels of c-di-GMP to regulate cognate cellular response. Uncovering the details of the regulation of the c-di-GMP signalling pathway is vital for understanding the behaviour of the pathogen and characterization of novel targets for anti-biofilm interventions.